2005
DOI: 10.1103/physrevlett.94.016804
|View full text |Cite
|
Sign up to set email alerts
|

Alloy Formation of Supported Gold Nanoparticles at Their Transition from Clusters to Solids: Does Size Matter?

Abstract: Gold nanoclusters of a size approaching the molecular limit (<3 nm) were prepared on Si substrates in order to study alloy formation on the nanometer scale. For this purpose, indium atoms are deposited on top of the gold particles at room temperature and the formation of AuIn(2) is studied by x-ray photoelectron spectroscopy in situ. It is observed that the alloy formation takes place independent of whether the particles electronically are in an insulating molecular or in a metallic state. Most important, howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
111
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(126 citation statements)
references
References 24 publications
14
111
1
Order By: Relevance
“…In the as-prepared state, a binding-energy position of 707.6 eV can be recognized, which nearly matches the value of 707.5 eV found for a clean Fe 48 Pt 52 reference film, but which significantly differs from the value observed for a pure Fe reference film (707.0 eV). When taking into account a final state effect induced by the photoemission process itself (emission of a photoelectron from a positively charged nanometer-sized capacitor), which leads to shifts of about 0.1 eV to higher binding energies for particle sizes of about 10 nm, [29] perfect agreement is found between the bulk alloy and the alloyed nanoparticles, indicating the mixing of Fe and Pt atoms on the atomic scale. This finding is also confirmed by analyzing the alloy-induced chemical shift of the Pt 4f core doublet (not shown here).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…In the as-prepared state, a binding-energy position of 707.6 eV can be recognized, which nearly matches the value of 707.5 eV found for a clean Fe 48 Pt 52 reference film, but which significantly differs from the value observed for a pure Fe reference film (707.0 eV). When taking into account a final state effect induced by the photoemission process itself (emission of a photoelectron from a positively charged nanometer-sized capacitor), which leads to shifts of about 0.1 eV to higher binding energies for particle sizes of about 10 nm, [29] perfect agreement is found between the bulk alloy and the alloyed nanoparticles, indicating the mixing of Fe and Pt atoms on the atomic scale. This finding is also confirmed by analyzing the alloy-induced chemical shift of the Pt 4f core doublet (not shown here).…”
mentioning
confidence: 58%
“…velocity, temperature), which, in case of Au nanoparticles, is known to result in a much better quality of the final array. [19,20,29] Further improvements can be expected by applying a template-based technique that was proposed previously [17] where spherical block-copolymer microdomains could successfully be organized with a high degree of topographical order into prepatterned template structures. Thus, based on its flexibility to easily modify relevant parameters like particle size, interparticle spacing, composition, and purity, we expect the micellar approach to have both, a strong impact on fundamental research related to magnetic nanoparticles organized into arrays, and a high potential for applications related to ultrahigh-density data-storage media.…”
mentioning
confidence: 97%
“…These shifts are interpreted as the final state effects caused by a positive charge induced by photoemission into electrically isolated particles. [16][17][18][19] Thus, the observed features strongly suggest the presence of sufficiently electrically isolated Pd nanoparticles. Figure 2 shows the Pd 3d spectra of the catalysts and the reference samples.…”
Section: A Valence Band Photoemissionmentioning
confidence: 77%
“…Numerous studies have found that the binding energy of metal clusters decreases with an increase of the cluster size, and it finally converges to the bulk value at large particle sizes. [60][61][62][63] For example, gold clusters with a particle size of approximately 0.6 nm show a binding energy that is + 0.8 eV higher than the one of bulk gold, [61] whereas clusters greater than 10 nm exhibit a binding energy that is < 0.1 eV compared to bulk gold. Following this trend, the binding energy www.chemeurj.org of Au nanoclusters in Au/HY and Au/HY-200 should present at the position larger than 84.2 eV.…”
Section: Resultsmentioning
confidence: 99%